Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{3}{5}\times y+\frac{1}{2}:\frac{5}{3}-\frac{5}{4}=\frac{1}{2}\times\frac{1}{3}\)
\(\Rightarrow\frac{3}{5}\times y+\frac{3}{10}-\frac{5}{4}=\frac{1}{6}\)
\(\Rightarrow\frac{3}{5}\times y+\left(-\frac{19}{20}\right)=\frac{1}{6}\)
\(\Rightarrow\frac{3}{5}\times y=\frac{67}{60}\)
\(\Rightarrow y=\frac{67}{36}\)
b) \(\frac{4}{5}:y+\frac{1}{4}\times\frac{1}{6}-\frac{1}{2}=\frac{1}{3}\times\frac{5}{2}\)
\(\Rightarrow\frac{4}{5}:y+\frac{1}{24}-\frac{1}{2}=\frac{5}{6}\)
\(\Rightarrow\frac{4}{5}:y+\left(-\frac{11}{24}\right)=\frac{5}{6}\)
\(\Rightarrow\frac{4}{5}:y=\frac{5}{6}+\frac{11}{24}=\frac{31}{24}\)
\(\Rightarrow y=\frac{4}{5}:\frac{31}{24}=\frac{96}{155}\)
c) \(\frac{3}{5}\times y-\frac{4}{5}:3+\frac{1}{12}=\frac{3}{2}+\frac{1}{5}\)
\(\Rightarrow\frac{3}{5}\times y-\frac{4}{15}+\frac{1}{12}=\frac{17}{10}\)
\(\Rightarrow\frac{3}{5}\times y-\frac{4}{15}=\frac{97}{60}\)
\(\Rightarrow\frac{3}{5}\times y=\frac{113}{60}\)
\(\Rightarrow y=\frac{113}{36}\)
a) \(\frac{27}{36}=\frac{3}{4}\)
b) \(\frac{45}{60}=\frac{3}{4}\)
c) \(\frac{2}{4}=\frac{1}{2}\)
d) \(\frac{10}{12}=\frac{5}{6}\)
e) \(\frac{112}{252}=\frac{4}{9}\)
Đúng nha bạn !!@@
\(\frac{1}{3}+\frac{3}{4}x\frac{5}{9}=\frac{1}{3}+\frac{5}{12}=\frac{3}{4}\)
\(\frac{7}{12}-\frac{5}{4}x\frac{2}{15}=\frac{7}{12}-\frac{1}{6}=\frac{5}{12}\)
\(y+\frac{1}{4}=\frac{7}{8}-\frac{3}{8}=y+\frac{1}{4}=\frac{1}{2}=\frac{1}{2}-\frac{1}{4}=\frac{1}{4}\)
\(y-\frac{5}{12}=\frac{2}{3}-\frac{1}{4}=y-\frac{5}{12}=\frac{5}{12}=\frac{5}{12}+\frac{5}{12}=\frac{5}{6}\)
\(\frac{12}{7}xy=\frac{16}{21}=\frac{16}{21}:\frac{12}{7}=\frac{4}{9}\)
\(\frac{5}{4}:y=\frac{7}{12}=\frac{5}{4}:\frac{7}{12}=\frac{15}{7}\)
Bài 1 :
A = 1 - 1/2 + 1/2 - 1/4 + 1/4 - 1/8 + 1/8 - 1/16 + ... + 1/32 - 1/64
A = 1 - 1/64
A = 63/64
12/3 x Y = 12/1
Y = 12/1 : 12/3
Y = 3
\(\frac{1}{6}+\frac{5}{6}=\frac{6}{6}=1\)
\(\frac{25}{5}+\frac{2}{6}=\frac{150}{30}+\frac{10}{30}=\frac{160}{30}=\frac{32}{6}=\frac{16}{3}\)
\(\frac{12}{5}+\frac{6}{9}=\frac{108}{45}+\frac{30}{45}=\frac{138}{45}\)
Ta có \(x.a=b\)
\(x=b:a\)
Do đó \(-\frac{3}{5}.x=\frac{5}{6}\)
\(x=\frac{5}{6}:\frac{-3}{5}\)
\(x=-\frac{1}{2}\)
Tương tự
2. \(x=\frac{6}{8}:\frac{2}{4}=\frac{3}{2}\)
Bạn tự làm câu 3
1.\(\frac{-3}{5}\).x=\(\frac{5}{6}\)
x=\(\frac{5}{6}\):\(\frac{-3}{5}\)
x=\(\frac{-25}{18}\)
2.\(\frac{2}{4}\):x=\(\frac{6}{8}\)
\(\frac{1}{2}\):x=\(\frac{3}{4}\)
x=\(\frac{1}{2}\):\(\frac{3}{4}\)
x=\(\frac{2}{3}\)
3.\(\frac{67}{89}\).x=\(\frac{12}{13}\)
x=\(\frac{12}{13}\):\(\frac{67}{89}\)
x=\(\frac{1068}{871}\)
K MIK NHÉ
\(\frac{5}{12}:\frac{6}{y}=\frac{1}{2}\)
\(\frac{6}{y}=\frac{5}{12}:\frac{1}{2}\)
\(\frac{6}{y}=\frac{5}{6}\)
\(y=6.6:5\)
\(y=\frac{36}{5}\)
Hk tốt